2018
DOI: 10.1016/j.bone.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The reduced osteogenic potential of Nf1-deficient osteoprogenitors is EGFR-independent

Abstract: Neurofibromatosis type 1 (NF1) is a common genetic disorder caused by mutations in the NF1 gene. Recalcitrant bone healing following fracture (i.e. pseudarthrosis) is one of the most problematic skeletal complications associated with NF1. The etiology of this condition is still unclear; thus, pharmacological options for clinical management are limited. Multiple studies have shown the reduced osteogenic potential of Nf1-deficient osteoprogenitors. A recent transcriptome profiling investigation revealed that ERE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Previous study conducted by Kuorilehto et al associated the NF1 gene expression with mouse fracture healing and rat pseudarthrosis, 14 and reported normal NF1 function was needed to achieve a normal bone fracture healing. When NF1 function is impaired, reduced osteogenic activity is seen in NF1 ‐deficient model 15 . In our current study, we found reduced NF1 expression in non‐union bones as compared to normal fracture bones, supporting the theory that NF1 is critical in bone fracture healing process.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous study conducted by Kuorilehto et al associated the NF1 gene expression with mouse fracture healing and rat pseudarthrosis, 14 and reported normal NF1 function was needed to achieve a normal bone fracture healing. When NF1 function is impaired, reduced osteogenic activity is seen in NF1 ‐deficient model 15 . In our current study, we found reduced NF1 expression in non‐union bones as compared to normal fracture bones, supporting the theory that NF1 is critical in bone fracture healing process.…”
Section: Discussionsupporting
confidence: 81%
“…When NF1 function is impaired, reduced osteogenic activity is seen in NF1-deficient model. 15 In our current study, we found reduced NF1 expression in non-union bones as compared to normal fracture bones, supporting the theory that NF1 is critical in bone fracture healing process. Autophagy is the process that allows cells to recycle damaged cellular components, and it plays an essential role in multiple tissue functions such as liver 16 and bone, 17 as well as in diseases such as cancers.…”
Section: Previous Study Conducted By Kuorilehto Et Al Associated the Nf1supporting
confidence: 87%
“…However, the residual ramus had been resorbed. regeneration and bone repair of patients with NF1 (11). This condition may be involved in bone malformations of these patients.…”
Section: Impact Of Mutation Of the Nf1 Gene On Bone Regenerationmentioning
confidence: 97%
“…In addition to coding RNAs, these super-enhancers have been reported to drive the expression of long non-coding RNAs such as MALAT1 (39), and microRNAs such as MIR663B (40) and MIR21 (41), which have been reported to contribute to osteosarcoma malignancy. In addition, some lineage-specific transcription factors which regulate skeletal development, such as GLI2 (42), LIF (43), MDM2 (44), RUNX2 (45), and EGFR (46), were found to be associated with super-enhancers ( Fig. 1A and C).…”
Section: Characterization Of Super-enhancers In Osteosarcoma Cellsmentioning
confidence: 99%